The Influence Of Marketing Mix On Customer Loyalty At Indomaret In The Talang Empat Area Of Central Bengkulu - M.Wahyu Fadyllah Syahputra; Ida Ayu Made ER Meytha; Nurzam Nurzam (Penerbit Jurnal Indonesia, 2023)
Marketing is one of the starting points for introducing products to customers and this will be very important because it will be related to the benefits that will be obtained by the business. This research aims to determine the effect of location, price, product and promotion on customer’s loyalty at Indomaret in the region of Talang Empat in Central Bengkulu Regency. This type of research is correlational, namely research to determine the effect and level of effect between two or more variables without any attempt to influence these variables. The sample in this study used an accidental sampling technique, where the population was sampled at Indomaret in the region of Talang Empat in Central Bengkulu Regency when researchers conducted research totaling 105 people. Based on the results of research on the effect of location, product, price and promotion on customer’s loyalty at Indomaret in the region of Talang Empat in Central Bengkulu Regency, the results obtained are that the F sig. value is 0.006 < 0.05 and and Fcount> Ftable (8.028> 2.47), therefore it can be concluded that together The same location, product, price and promotion influenced the customer’s loyalty at Indomaret in the region of Talang Empat in Central Bengkulu Regency.